Worship From Home : Merenda Iman di GMIT Oebobo Kupang - Hemi D. Bara Pa; Christofel Saetban; Misael Boineno; Noldiana Luin; Nelci Nafalia Ndolu (Institut Agama Kristen Negeri Kupang, 2021)
Covid-19 demands the attitude of the Kupang Peniel Oebobo Church community which is characterized by Calvinism in worship. The purpose of this study was to determine the attitude of the Pniel Oebobo church community in responding to Worship From Home during the Covid-19 pandemic. In addition, seeing the possible positive impact of worship from home for the spirituality of the community. This research was conducted using Frans Wijsen's qualitative research matrix, namely